Productivity Enhancement through Production Monitoring System - H C Shiva Prasad; Potti Srinivasa Rao; B Gopalkrishna; Aakash Ahluwalia (International Journal of Applied Business and Economic Research, 2016)
A production monitoring system uses the real time data while production is online. The real time production monitoring systems are designed as means of auto data to collection and monitoring the data via display boards. This study focuses on analysing the real time production monitoring systems through trend analysis in production and over consumption of raw material controlling the over consumption's in a pen manufacturing industry. Methodology followed is through process flow diagram, collection of data, analysis of data. Pre and post analysis was conducted to identify the factors responsible for over consumption and causal factors responsible for the over consumption were identified to reduce the cost of consumption by 58% with introduction of production monitoring system.
Keywords: M11; 330; consumption; pre and post factors; production monitoring system; productivity